2020
DOI: 10.1186/s13048-020-00720-w
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-1271-5p/TIAM1 suppresses the progression of ovarian cancer through inactivating Notch signaling pathway

Abstract: Objective Ovarian cancer (OC) has been regarded as the most malignant gynecological neoplasm and often confers grave outcomes owing to the frequent metastasis and high recurrence. A previous study has demonstrated that miR-1271-5p is implicated in OC progression, however, the possible mechanism of it remains unknown. The purpose of this investigation was to explore how miR-1271-5p regulates the progression of OC. Methods Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) databases were employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Previous studies have suggested that miR-1271-5p is closely associated with the progression of several malignancies. Han et al found that miR-1271-5p suppressed the progression of ovarian cancer through Notch signaling [ 29 ]. Furthermore, it was reported that MALAT1 sponges miR-1271-5p and facilitates multiple myeloma and ovarian cancer progression by regulating SOX13 and E2F5, respectively [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that miR-1271-5p is closely associated with the progression of several malignancies. Han et al found that miR-1271-5p suppressed the progression of ovarian cancer through Notch signaling [ 29 ]. Furthermore, it was reported that MALAT1 sponges miR-1271-5p and facilitates multiple myeloma and ovarian cancer progression by regulating SOX13 and E2F5, respectively [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MALAT1 has been reported to modify ccRCC progression via regulating miR-194-5p/ACVR2B signaling [28]. Previous studies have suggested that miR-1271-5p is closely associated with the progression of suppressed the progression of ovarian cancer through Notch signaling [29]. Furthermore, it was reported that MALAT1 sponges miR-1271-5p and facilitates multiple myeloma and ovarian cancer progression by regulating SOX13 and E2F5, respectively [30,31].…”
Section: Disease Markersmentioning
confidence: 99%
“…miR-1271-5p knockdown promoted the proliferative ability of ovarian cancer cells. Levels of HES1 and NOTCH were noted to be reduced in miR-1271-5p-expressing ovarian cancer cells (46).…”
Section: Satb1 (Special At-rich Sequence-binding Protein 1) Directly ...mentioning
confidence: 92%
“…TIAM1 (T cell lymphoma invasion and metastasis-1) promoted NOTCH pathway and consequently enhanced invasion of ovarian cancer cells (46). miR-1271-5p acted as a tumor suppressor and targeted TIAM1.…”
Section: Satb1 (Special At-rich Sequence-binding Protein 1) Directly ...mentioning
confidence: 99%
“…miR-223 and miR-1275 promoted cancer occurrence and development by activating the Notch signaling pathway [ 64 , 65 ]. miR-1271-5p and miR-34 suppressed the proliferation, invasion, and migration of cancer cells by blocking the Notch signaling cascade [ 66 , 67 ]. miR-139-5p and miR-199b-5p could sensitize cancer cells to chemotherapeutic agents by reducing the activity of the Notch1 signaling [ 68 , 69 ].…”
Section: Roles Of Main Noncoding Rnas In Cancermentioning
confidence: 99%